Research on Concentration and Chemical Speciation of Heavy Met-Als in Urban Soils of Warri, Nigeria - Ataikiru, Helen; Okieimen, F. E.; Uwumarongie, E. G. (Challenging Issues on Environment and Earth Science Vol. 3, 2021)
The pseudo total and chemical speciation of manganese, chromium, lead and Zinc were determined by a chemical method (1) and Tessier's method [1] respectively to ascertain if significant concentration of the metals are mobile and bioavailable in Urban Soils of Warri. Intervention values were calculated to known if the metal contamination has reached the level that the soils should be treated. Ten soil samples from five sites (Esisi, Apala, Airport Road, Ugborikoko and NPA Expressway Refuse dumps) were collected (5 top soils 0 -15 and 5 bottom soils 15 - 30 cm) using a stainless steel augur. Sample solutions prepared were analysed using the Atomic Absorption spectrophotometer technique. Results showed that mean values of total heavy metals for the top soils are 4. 00 ± 0.00 to 111.00 ± 7. 00 ppm Mn, 9. 13± 0.13 to 292. 28 ± 7.82 ppm Cr, <0.08 to 493. 00 ± 3.00ppm Pb, 35.00 ± 0.00 to 1012.00+ 2.00ppm Zn. Bottom soil samples contain as much as 7.00 ± 0,00 to 160. 00 ±0.00 ppm Mn, 35.05 ± 0.40 to 263.00 ± 0.00ppm Cr, <0.08 to 286.00 ± 6.00ppm Pb and 64.00 ± 4.00 to 1458.00 ± 8.00ppm Zn. The values reported had an abundance ratio in the order Zn >Cr > Mn > Pb. The values reported in this study are higher than Federal Environmental Protection Agency (3) values in some of the soil samples. The intervention values obtained are 190.40mg/kg Cr. 312.10 mg/kg Pb and 257.67 mg/kg Zn. Total Zn is higher than intervention values in all the soil samples, total Cr-is close to intervention value while Pb is lower than intervention value. Chemical properties such as pH total organic carbon and CEC were also analyzed. Six soil samples (3 top soils and 3 bottom soils) from three sites (Esisi, Apala and NPA Expressway dump sites)'were selected and analysed for chemical partitioning using Tessier's procedure. The results showed that the metals showed highest concentration in the Fe-Mn oxide fraction except Pb. Pb is not associated to the exchangeable phase. The metals showed significant concentration in the non-residual fraction except Pb. This shows that significant concentration of the metals are mobilo and bioavailable to plants and other ecological materials. The bioavailable values reported in this study are higher than the values reported for uncontaminated soils. [2] Cr, Zn and Mn contents in the soils are also positively correlated to the pH of the soil. Chemical speciation is defined as distribution of an individual chemical element among different species or groups. Trace metals may be distributed among many components of the soil and may be associated with them in different ways.